Congruence between selection on breeding values and farmers’ selection criteria in sheep breeding under conventional nucleus breeding schemes - Gizaw, Solomon; Getachew, T.; Tibbo, Markos; Haile, Aynalem; Dessie, Tadelle (Elsevier, 2011)
Designing breeding schemes suitable for smallholder livestock production systems in developing regions has hitherto been a challenge. The suggested schemes either do not address farmers’ breeding goals (centralized station-based nucleus schemes) or yield slow genetic progress (village-based schemes). A new breeding scheme that integrates the merits of previously suggested schemes has been designed for Menz sheep improvement in Ethiopia. It involves selection based on breeding values in nucleus flocks to produce elite rams, a one-time only provision of improved rams to villagers and a follow-up village-based selection to sustain genetic progress in village flocks. Here, we assessed whether conventional selection of breeding rams based on breeding values for production traits, which is the practice in station-based nucleus flocks, meets farmers’ breeding objectives. We also elicited determinants of farmers’ ram choice. Low but significant correlations were found between rankings of rams based on farmers’ selection criteria, estimated breeding values (EBV) and body weight (BW). Appearance traits (such as color and horn) and meat production traits (BW and linear size traits) significantly determined farmers’ breeding ram choice. The results imply that conventional selection criteria based solely on EBV for production traits do not address farmers’ trait preferences fully, but only partially. Thus, a two-stage selection procedure involving selection on breeding values in nucleus centers followed by farmers’ selection among top- ranking candidate rams is recommended. This approach accommodates farmers’ preferences and speeds up genetic progress in village-based selection. The Menz sheep scheme could be applied elsewhere with similar situations to transform conventional station-based nucleus breeding activities into participatory breeding programs.